العلاقات العامة الالكترونية ودورها في تحسين صورة المؤسسات الناشئة مؤسسة YA TECHNOLOGIES دراسة حالة - مزياني, زينب (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
تهدف الدراسة الى ابراز دور العلاقات العامة الالكترونية في تحسين صورة المؤسسات الناشئة والحديثة تكنولوجيا، باعتبار العلاقات العامة الالكترونية عملية اتصالية تفاعلية متكاملة الأركان، وأكثر فاعلية في تحسين الصورة وتسهيل تواصل المؤسسة مع جماهيرها، انطلاقا من دراسة حالة لمؤسسة YA TECHNOLOGIES الناشئة، وتنتمي الدراسة الى نوع الدراسات الكيفية نسبة الى المنهج المستخدم منهج دراسة حالة، حيث تم توظيفه للإجابة على المشكلة التالية:كيف تساهم العلاقات العامة الالكترونية في تحسينها لصورة مؤسسة YA TECHNOLOGIES الناشئة؟ ، وتوصلت الدراسة الى جملة من النتائج أهمها: تلعب العلاقات العامة الالكترونية دورا حيويا وديناميكيا لبناء الصورة الذهنية وادارتها للمؤسسة الناشئة . كلمات المفتاحية: العلاقات العامة الالكترونية؛ الصورة الذهنية؛ المؤسسة؛ المؤسسات الناشئة Abstract: The study aims to highlight the role of electronic public relations in improving the image of emerging and modern institutions in technology, considering electronic public relations an interactive, integrated process of communication, and more effective in improving the image and facilitating the institution’s communication with its audiences, based on a case study of the emerging YA TECHNOLOGIES, and the study belongs to a type Qualitative studies relative to the method used is a case study approach, which was employed to answer the problem posed in the form of a main question: How does electronic public relations contribute to improving it to the image of the emerging YA TECHNOLOGIES? The study reached a number of results, the most important of which are: Electronic public relations play a vital and dynamic role in building and managing the mental image of the emerging Keywords: Electronic public relations ; mental image ; institution ; startups.